Development of rice food products with long shelf-life effects of soaking time and rice variety on the quality of rice cookies - Dela Cruz, Soledad Nalupta (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2000)
The study was conducted to develop a rice food product which has long shelf-life and can be produced easily by small scale entrepreneurs such as groups housewives and out-of-school youth. The said product is intended to increase the value of rice having multi-food products such as cookies made from pure rice flour whichcan be sold in the shelves of supermarkets and variety stores. Three lowland rice varieties with high yield potential in the province of Ilocos Norte were used in the study, namely: PSB Rc22, PSB Rc 28, QND PSB Rc 30. Of the three varieties tested, PSB Rc 28 was found to be the ideal variety for rice cookies. The cookies made out of this variety were rated as moderate to very crunchy,slight to moderately fine texture, moderately golden yellow which is the desirable color, moderately rich buttery taste, moderately buttery smell, and a general acceptability rating of 7.22 in scale of 9 which means between "like moderately" to "like very much". There was no significant effect of soaking time on the texture of the rice flour and eventually the rice cookies. However, PSB Rc 28, the optimun time soaking is four hours. This is the time in which the cookies produced form this variety were found to have the desired color and taste.